A dual soft-template synthesis of hollow mesoporous silica spheres decorated with Pt nanoparticles as a CO oxidation catalyst. Issue 119 (19th November 2015) - Li, Yunqi; Bastakoti, Bishnu Prasad; Abe, Hideki; Liu, Zongwen; Minett, Andrew; ALOthman, Zeid A.; Yamauchi, Yusuke
Abstract : Hollow mesoporous silica spheres decorated with fine Pt nanoparticles are prepared through a dual soft-template system and used as a catalyst for high-temperature CO oxidation. Abstract : Hollow mesoporous silica (HMS) decorated with fine Pt nanoparticles is directly prepared through a dual soft-template system using a triblock copolymer, poly(styrene- b -2-vinyl pyridine- b -ethylene oxide), and a cationic surfactant, cetyltrimethylammonium bromide. The Pt nanoparticles of uniform particle size are stably embedded inside the mesoporous silica shell and possess both a huge surface area and a large total pore volume. The Pt nanoparticles supported by the mesoporous silica exhibit excellent thermal stability, which enables their application in high-temperature CO oxidation.